THE CORRELATION BETWEEN STUDENT’S VOCABULARY MASTERY AND READING COMPREHENSION - Syahruni Ramadani; Saiful; Awalia Azis (FKIP Unismuh Makassar, 2021)
This study aimed to investigate (1) How student performance in vocabulary mastery (2) How student performance in reading comprehension (3) Is there any correlation between student’s vocabulary mastery and reading comprehension. This research used a descriptive research method. The researcher focused on the correlation between vocabulary mastery and reading comprehension at XI grade MAN Selayar. The number of sample was 24 students and used random sampling technique. The researcher used test as instrument. In addition, the data collection techniques used a questionnaire. The researcher finding was found that the vocabulary mastery of the XI grade of MAN Selayar was categorized into poor. It was indicated by the mean score (82.20) and the students reading comprehension was categorized fair. It was indicated by the mean score (84.64). Meanwhile, the results of the correlation were found with the results of 0.914. From these results it has been concluded that the correlation between vocabulary mastery and reading very strong. Because based on the product moment the correlation value calculation formula is 0.914, and that has included very strong value.